Evaluation of Clinical and Instrumental Results of Patients with a Risk of Development of Recurrent Mission - A. , Sultonova N. (Central Asian Journal of Medical and Natural Science, 2023)
PNP is one of the most urgent problems of modern medicine. Despite a long study of the problem of miscarriage, the etiological factors, pathogenetic mechanisms of spontaneous miscarriage have not yet been fully disclosed. The main difficulty in determining the immediate cause of abortion is due to the fact that miscarriage is a multifactorial process in which some factors may be of paramount importance, while others will be the background. In practice, in a particular clinical case, it can be quite difficult to separate them. Obviously, the causes of miscarriage must be considered in the light of the causes of deterioration in reproductive health in general.